Dialogues in Promoting Knowledge Construction - Bo Chang (Adult Education Research Conference, 2017)
This study examined how different types of dialogues promoted knowledge construction in an online course. Findings show that instructor designed the online discussion questions which balanced the grounding dialogue, critical dialogue and reflective dialogues. Three types of dialogues were interwoven together to help students understand the topics from various dimensions. Giving students freedom to select readings and discussion questions, creating a safe environment, and providing practical and controversial materials give space for different types of dialogues to flourish, and are crucial for stimulating the active and proactive knowledge sharing and creation.
Keywords: Online dialogues; knowledge construction